2013
DOI: 10.1186/1475-2840-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of carotid atherosclerosis in newly diagnosed patients with ketosis-onset diabetes: a cross-sectional study

Abstract: BackgroundThe features of carotid atherosclerosis in ketosis-onset diabetes have not been investigated. Our aim was to evaluate the prevalence and clinical characteristics of carotid atherosclerosis in newly diagnosed Chinese diabetic patients with ketosis but without islet-associated autoantibodies.MethodsIn total, 423 newly diagnosed Chinese patients with diabetes including 208 ketosis-onset diabetics without islet-associated autoantibodies, 215 non-ketotic type 2 diabetics and 79 control subjects without di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 46 publications
9
62
2
Order By: Relevance
“…Similar to our previous and other studies [22,42-44], we found that older patients (age ≥ 65) had a higher mean CIMT and prevalence of carotid plaque compared with younger patients (age < 65) in each UACR tertile group. Gender difference in carotid atherosclerosis has been confirmed in general population and patients with diabetes [34,35,45], but in the present study, sex-related differences in the mean CIMT and in the prevalence of carotid plaque existed only in the highest UACR tertile group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our previous and other studies [22,42-44], we found that older patients (age ≥ 65) had a higher mean CIMT and prevalence of carotid plaque compared with younger patients (age < 65) in each UACR tertile group. Gender difference in carotid atherosclerosis has been confirmed in general population and patients with diabetes [34,35,45], but in the present study, sex-related differences in the mean CIMT and in the prevalence of carotid plaque existed only in the highest UACR tertile group.…”
Section: Discussionsupporting
confidence: 91%
“…Plaque within the carotid artery was defined as a localized protrusion of the internal part of the vessel wall into the lumen of 50% of the surrounding IMT value [21]. Carotid stenosis was defined as any degree of narrowing of the carotid arteries by carotid plaques [22]. …”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study was partly based on data used in our previous study15161718. Briefly, 3 598 inpatients with type 2 diabetes mellitus were consecutively observed.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were interviewed to obtain their history of hypertension (HTN), cardio-cerebrovascular events (CCEs), medicine use including metformin, lipid-lowering drugs (LLDs), antihypertensive agents (AHAs) and insulin or insulin analogues (IIAs), alcohol consumption and smoking habits. The definitions of smoking, alcohol consumption, and HTN were based on our previous criteria1516. The definition of CCEs was also according to our previous study1518.…”
Section: Methodsmentioning
confidence: 99%
“…The role of ketones in contributing to the risk of development of cardiovascular disease (CVD) is not known. Nevertheless, there is some evidence that elevated ketone levels are associated with congestive heart failure and carotid atherosclerosis [12,13]. On the other hand elevated blood ketones are associated with the worsening of hyperglycemia, and patients with ketosis onset T2D showed much more severe insulin resistance compared to nonketotic onset T2D patients [14,15].…”
Section: Introductionmentioning
confidence: 99%